EFEKTIVITAS MODEL PEMBELAJARAN ECOLITERACY DAN ADAPTASI (ELA) DALAM MENINGKATKAN KREATIVITAS BELAJAR IPAS PADA SISWA KELAS V DI SD N 1 PADOKAN - Kumala Dewi, Adelia Febi; Hermawan Wahyu Setiadi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to analyze the effectiveness of the Ecoliteracy and Adaptation (ELA) learning model in improving fifth-grade students’ creativity in Integrated Science and Social Studies (IPAS) at SD N 1 Padokan. This research employed a quantitative approach using a quasi-experimental method with a nonequivalent control group design. The research subjects consisted of 46 students who were divided into an experimental class and a control class, each consisting of 23 students. Data were collected using a creativity test instrument based on fluency, flexibility, originality, and elaboration indicators, which had been validated and tested for reliability. The data were analyzed using descriptive statistics, normality and homogeneity tests, and an independent sample t-test. The results showed that the mean score of the experimental class increased from 62.283 in the pre-test to 74.565 in the post-test, while the control class mean score changed from 65.000 to 64.565. The independent sample t-test revealed a significance value of 0.007 (p < 0.05), indicating a significant difference between the two groups. These findings demonstrate that the Ecoliteracy and Adaptation (ELA) learning model is effective in enhancing students’ creativity in IPAS learning. The implementation of contextual and environment-based learning encourages students’ active engagement and supports the development of 21st-century skills, particularly creativity.